1968
DOI: 10.2307/2325917
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Share Repurchase on the Value of the Firm: Reply

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…Based on above results it may be concluded that stock repurchase is still the best option for investors to distribute the excess fund, as we have seen that the indicators of investors based valuation also supported this issue. This result is in line with the results from Elton & Gruber (1968) whereas in any corporation's there will usually be some stockholders who will lean cash dividends and some who will incline stock repurchase as a method of cash disbursement. Based on the t test to assess whether there was a linear in luence of the independent variables undervaluation (X1), leverage (X2), free cash low (X3) and dispersion of ownerships (X4) toward company's stock repurchase (Y ), the study has shown that leverage and dispersion of ownerships show a positive and signi icant in luence toward the company's stock repurchase.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Based on above results it may be concluded that stock repurchase is still the best option for investors to distribute the excess fund, as we have seen that the indicators of investors based valuation also supported this issue. This result is in line with the results from Elton & Gruber (1968) whereas in any corporation's there will usually be some stockholders who will lean cash dividends and some who will incline stock repurchase as a method of cash disbursement. Based on the t test to assess whether there was a linear in luence of the independent variables undervaluation (X1), leverage (X2), free cash low (X3) and dispersion of ownerships (X4) toward company's stock repurchase (Y ), the study has shown that leverage and dispersion of ownerships show a positive and signi icant in luence toward the company's stock repurchase.…”
Section: Discussionsupporting
confidence: 84%
“…Based on above results it may conclude that stock repurchase can still be the best option for investors to distribute the excess fund, as we have seen that the indicators of investors based valuation also supported this issue. This research result is in line with the results from Elton & Gruber (1968) who commented that some of the companies' shareholders will prefer to choose cash dividends and alternate stockholders might prefer to choose the stock repurchase for their money disbursement technique purposed. Therefore, the factors of the independent variables undervaluation (X1), leverage (X2), free cash low (X3) and dispersion of ownership (X4) are still becoming the best consideration for stockholders in performing stock repurchase, thus, also supporting that the purpose of stock repurchase is to recover the decline of stock value.…”
Section: Hypothesis Test-f -Testsupporting
confidence: 88%
“…Share repurchases lead to stock price appreciation and subsequently to capital gains, which are taxed differently from cash dividends. In the past, the tax rate on capital gains used to be lower than that on cash dividends (e.g., Bierman and West, 1966, 1968; Elton and Gruber, 1968a, 1968b). This still holds for some countries, such as the US, but other countries, such as Germany, now use the same tax rate for cash dividends and capital gains.…”
Section: Introductionmentioning
confidence: 99%